Application of the QBRs Index for riparian habitat quality assessment along Sugut River, Sabah, Malaysia - NICHOLAS FONG VUI CHIK; ELIA GODOONG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Chik NFV, Godoong E. 2025. Application of the QBRs index for riparian habitat quality assessment along Sugut River, Sabah, Malaysia. Biodiversitas 26: 4137-4145. Riparian zones, which are crucial for biodiversity and ecosystem services, are increasingly threatened by land use changes, encroachment, and erosion. This study applied the QBRs (Qualitat del Bosc de Ribera-Sabah adaptation) Index to assess the ecological condition of riparian zones along a 245 km stretch of Malaysia's Sugut River. A total of 120 plots (50×50 m each) were evaluated using satellite imagery and field assessments, focusing on canopy cover, vegetation structure, riparian habitat quality, and channel alterations. QBRs scores ranged from 25 to 100. Overall, only 2% of plots were classified in natural condition (?95), while 17% were good (75-90), 20% fair (55-70), 38% poor (30-50), and 23% very poor (?25). Despite the non-significant land-use effect, degradation was concentrated in the lower catchment, where semi-open canopies, shrub dominance, and oil palm cultivation were prevalent. The Kruskal-Wallis test revealed no statistically significant differences in QBRs scores across land-use types (?²: 4.3144, df: 3, p: 0.2295), indicating that riparian health may be influenced by factors beyond land use alone. These findings highlight the limited extent of intact riparian habitats in the Sugut River basin and underscore the urgent need for targeted ecological restoration, improved riparian buffer enforcement, and sustainable land-use planning. The study also demonstrates the practical utility of the QBRs Index as a rapid assessment tool for prioritizing conservation actions in tropical river systems. We recommend prioritizing restoration of areas scoring between fair, poor and very poor, strengthening enforcement of riparian zones, targeted replanting of native riparian trees and regular QBRs re-assessment to track recovery.